How Do These Knock-Knock Jokes Work? A Pragmatic Analysis of Humor - Indah Bunga Lestari; Wisasongko Wisasongko; Dewianti Khazanah (Journal of Language and Literature, 2025)
Humor practices have been approached using different theories. Some of the humor is universal, but it will be different when the cultural nuance interplays with it. This study aims to analyze the construction of humor in the Knock-Knock Jokes tweets on the comment section of an Indonesian base account on X, which was formerly known as Twitter, named @englishfess_, and the contribution of cultural context in creating the humorous effect in the jokes.  This study used Raskin's Script-Based Semantic Theory of Humor (SSTH) to analyze the types of humor used in the data and Grice's Theory of Maxim to analyze the flouting of maxims in the creation of the jokes, as well as the cultural context theory. Using a qualitative research method, this study collected 20 data in the form of snapshots of X users' tweets in the comment section. It was found that the humor of the Knock-Knock Jokes tweets mostly comes from the use of incongruity types of humor, the flouting of the maxim of relation, and the cultural contexts. As the punchlines of the jokes frequently used certain Indonesian cultures, these Knock-Knock Jokes tweets have a unique humor, and may only be understood by those who have a similar cultural background to the tweeters of the joke.